letter to the editor about a published article DOI: 10.2196/mhealth.8458 - Johan Goris (2017)
The first half of 2026 has seen several nursing strikes in the United States, driven by persistent workforce shortages and increasing workloads and burden on nursing staff. In this News and Perspectives article, JMIR Correspondent Benedette Cuffari reports on whether emerging digital tools can address some of these pressures, speaking with an expert on important considerations for integrating these technologies into nursing practice.